Hubungan Asupan Lemak, Kalsium, Magnesium, dan Aktivitas Fisik dengan Derajat Dismenorea pada Mahasiswa Fakultas Ilmu Keolahragaan dan Kesehatan Universitas Negeri Surabaya - Novanda Isnain Ramadhani; Amalia Ruhana (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Dysmenorrhea is pain during menstruation experienced by women of childbearing age. Risk factors that can cause dysmenorrhea include age of menarche, family history, duration and menstrual cycle, stress, physical activity, nutritional status, and nutrient intake. Some nutrients that are related to the incidence of dysmenorrhea include fat, calcium, and magnesium. This study aims to determine the relationship between fat, calcium, magnesium, and physical activity intake with the severity of dysmenorrhea in students of the Faculty of Sport and Health Sciences, Surabaya State University. This study used a cross-sectional approach. The sampling technique used stratified random sampling with a total of 119 samples. Data collection used the NRS (Numeric Rating Scale) questionnaire for the incidence of dysmenorrhea, SQ-FFQ (Semi Quantitative Food Frequency) for fat, calcium, and magnesium intake, and IPAQ-SF (International Physical Activity Questionnaire-Short Form) for physical activity. The results showed that students of the Faculty of Sport and Health Sciences, Surabaya State University had low fat intake (79%), low calcium intake (58%), normal magnesium intake (47,9%), heavy physical activity (47,1%) and mild dysmenorrhea pain (40,3%). Data analysis using the Spearman Rank test showed a value of p = 0.000 (fat), p = 0.023 (calcium), p = 0.023 (magnesium), and p = 0.039 (physical activity). Based on the results of the study, it can be concluded that there is a significant relationship between fat, calcium, magnesium, and physical activity intake with the severity of dysmenorrhea (p <0.05).